Performance assessment of the fire safety of a NHA house model using fire dynamics simulation - Tan, Geocerie D.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Performance-Based Design (PBD) is a new approach being adapted with regards to fire safety engineering. In the Philippines, only few and limited developments and implementations regarding PBD have been made at present due to the lack of researches and studies being conducted. To address this, performance assessment will be conducted on a National Housing Authority (NHA) residential house with loft. From data gathered, fire scenarios were developed. For each scenario, area of origin was varied. Performance objectives were established, specifying performance criteria that would be evaluated at the end of each simulation. Fire modeling was then conducted using Computational Fluid Dynamics (CFD), specifically Fire Dynamics Simulation (FDS), with the program Pyrosim. In Pyrosim, fire smoke development, prediction of thermal flows, concentration of toxic substances released during the fire and other fire parameters estimation were simulated. Using the results from FDS, critical and safety conditions (and values representing them) that the house model may experience during a fire were determined to evaluate the perfonnance of the building. It was observed, based on critical time to reach threshold value ofthe performance criteria and visibility that the second scenario (living room as area of origin) produced the worst case for the house model. Other areas in the model were safe given the critical time. Duration of simulation may be extended to the maximum time needed for a fully protected zone (3600 s) to further evaluate the model. Methods used may also be applied to other performance objectives, fire scenarios and building models.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Fire risk assessment; Fire protection engineering; Model houses